Mobile App-Based Intervention for Adolescents With First-Episode Psychosis: Study Protocol for a Pilot Randomized Controlled Trial - Barbeito, Sara; Sánchez-Gutiérrez, Teresa; Mayoral, María; Moreno, Miguel; Rios-Aguilar, Sergio; Arango, Celso; Calvo, Ana (Frontiers in Psychiatry, 2019)
Introduction: Previous studies have shown an improvement in the access to treatment for patients with first-episode psychosis (FEP), specifically young patients, through mobile app-based interventions. The aim of this study is to test the effectiveness of a mobile app-based intervention to improve community functioning in adolescents with FEP. Mobile app-based interventions could increase quality of life and disease awareness, which improve adherence to treatment and reduce the frequency of relapses and rehospitalizations in adolescents with FEP. Methods: This article describes a mobile app treatment and the pilot trial protocol for patients with FEP. We will perform a single-blind randomized clinical trial (RCT) including patients with FEP aged 14-19 years recruited from Gregorio Mare& Hospital, Madrid, Spain. Patients will be randomly assigned to an intervention group, which will receive treatment as usual plus five modules of a psychological intervention through the mobile app (psychoeducation, recognition of symptoms and prevention of relapses, problem solving, mindfulness, and contact wall), or to a control group (standard care). The effectiveness of the intervention will be assessed by means of an extensive battery of clinical tests at baseline and at 3 months of follow-up. The primary outcome is reduction in psychotic and depressive symptoms; secondary outcomes comprise adherence, awareness, use of drugs, and quality of life. Data will be analyzed on an intention-to-treat (ITT) basis. Mixed model repeated-measures analysis will be used to explore the following effect: group x time interaction between the control group and the intervention group for clinical and functional variables during the follow-up period. Discussion: This is an innovative study for the assessment of a psychological intervention through a mobile app for patients with FEP during the critical period. This pilot RCT is intended to be a precursor to larger studies, which in turn could facilitate dissemination of mobile app therapy for patients with FEP. Ethics and Dissemination: The local ethics committee approved the study protocol. All participants must sign the informed consent, to participate. After finalizing the study, the results will be published.
Keywords: early onset psychosis; mobile treatment; psychotherapy; adolescents; online treatment; Scopus; JCR